2020
DOI: 10.7759/cureus.10248
|View full text |Cite
|
Sign up to set email alerts
|

Myasthenia Gravis and its Association With Thyroid Diseases

Abstract: Myasthenia gravis (MG) is a rare autoimmune neuromuscular junction disorder, and thyroid disorder is a disorder involving the thyroid receptor, of which Graves' disease (GD) is the most common autoimmune thyroid disorder, in which antibodies develop against thyroid receptors. Both may have similar clinical features. In myasthenia gravis, autoimmune antibodies develop against postsynaptic neuromuscular junction disrupting the neuromuscular transmission, resulting in fluctuating muscle weakness and fatigue. It i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 34 publications
(45 reference statements)
1
13
0
Order By: Relevance
“…Treating one pathology may worsen the other pathology. Therefore, physicians should always treat MG as a difference in patients with hyperthyroidism who have new symptoms of fatigue, respiratory failure or neuromuscular weakness [ 4 ]. Conditions such as operation and infection and such medicines as anesthetics, benzodiazepines, or even antibiotics may induce a myasthenia crisis.…”
Section: Discussionmentioning
confidence: 99%
“…Treating one pathology may worsen the other pathology. Therefore, physicians should always treat MG as a difference in patients with hyperthyroidism who have new symptoms of fatigue, respiratory failure or neuromuscular weakness [ 4 ]. Conditions such as operation and infection and such medicines as anesthetics, benzodiazepines, or even antibiotics may induce a myasthenia crisis.…”
Section: Discussionmentioning
confidence: 99%
“…This may be related to the fact that both of them share a common genetic background. 3 It has been shown in previous studies that the incidence of ocular MG is higher in cases of abnormal thyroid autoimmunity. 4 However, the prevalence of thyroid disease varies from study to study, and it is not yet known whether the clinical features and course of disease in these patients are different from those in patients without hyperthyroidism.…”
Section: Introductionmentioning
confidence: 94%
“…Many studies found that MG is associated with other autoimmune diseases, particularly autoimmune thyroid diseases: Graves' disease and Hashimoto's thyroiditis. 9 Several studies demonstrated an association between the presence of thymoma with the seropositivity to AChR antibody. 10 However, to the best of our knowledge, none of these studies have investigated the association between the quantitative measurement of AChR antibody titers and the presence of thyroid autoimmune antibodies or of thymoma, particularly in OMG patients.…”
Section: Introductionmentioning
confidence: 99%
“…Autoimmune thyroid diseases are associated with MG, with Graves' disease and Hashimoto's thyroiditis as the two most common such autoimmune diseases. 9 Amin et al reported a 2.36-fold increased risk of autoimmune thyroid diseases in MG patients. 9 However, to the best of our knowledge, no reports have shown an association between AChR antibody titer and the presence of thyroid autoimmune antibodies, particularly in OMG patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation